Elementary School Teachers’ Perception Using Stories in English Language Literacy - Melin Cahyani, Kadek; Ni Made Ratminingsih; Made Hery Santosa (Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to determine the perception of elementary school teachers on the use of stories in the learning process. This study used a mixed method involving 7 elementary school teachers from SD Negeri 3 Banjar Jawa and SD Laboratorium Undiksha as samples. Data collection was carried out through questionnaires and interviews. Questionnaires and interviews were made based on the theory of perception. Perception theory consists of behavioral, emotional, and cognitive engagement. The study results showed that most teachers had a very positive perception, with an average value of 23.90 on the use of stories. The results of the interview also stated that the results were very positive. In terms of behavior, teachers are able to involve themselves in the learning process to help increase students' interest in reading. In addition, emotionally, teachers are also able to organize the learning process so that students are comfortable and can teach moral values ​​to students through stories. Furthermore, in the cognitive aspect, teachers are very able to guide students in completing tasks that are arranged according to targets during the learning process. Based on the results of this study, researchers strongly recommend the use of stories to improve literacy. Teachers can use learning media that are relevant to the story and create a fun learning atmosphere.